Random Selection of Herbs and Weak Knowledge of Plants or Why Different Plants Were Used to Treat the Same Diseases in Slavic Folk Medicine - Kozłowska-Doda, Jadwiga (Slavistica Vilnensis, 2024)
SZCZEŚNIAK KRYSTYNA, 2022, Świat zamów światem roślin na pograniczu wschodniej i zachodniej Słowiańszczyzny, Gdańsk: Wydawnictwo Uniwersytetu Gdańskiego, s. 884.
Keywords: -